2022
DOI: 10.1136/military-2022-002106
|View full text |Cite
|
Sign up to set email alerts
|

Total hip and knee arthroplasty after lower extremity amputation in a military population

Abstract: IntroductionThe military includes lower extremity amputees requiring arthroplasty; however, there is little literature on this population. The primary aim of this study was to report demographics and clinical factors in amputees who undergo total hip or knee arthroplasty (THA/TKA) in the Military Health System (MHS). Second, patient-reported outcome measures (PROMs) are reported.MethodsThe Military Data Repository was queried for patients with lower extremity amputations and TKA or THA between 1 October 2014 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“… TKR Total knee replacement, Hemi Hip hemiarthroplasty, NOF Neck of femur, NB Two patients received a combination of arthroplasty (THR and TKR) and therefore are counted in both groups [ 25 , 35 ]. No sub-group demographic description of gender status in Li ADF et al, so incomplete gender demographics compared to total participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… TKR Total knee replacement, Hemi Hip hemiarthroplasty, NOF Neck of femur, NB Two patients received a combination of arthroplasty (THR and TKR) and therefore are counted in both groups [ 25 , 35 ]. No sub-group demographic description of gender status in Li ADF et al, so incomplete gender demographics compared to total participants.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 40 included studies, only 13 reported any post-operative complications.Where reported, complications included peri-prosthetic fracture [ 15 , 18 , 19 , 35 , 52 ], dislocation [ 15 , 18 , 19 ], infection (superficial and deep) [ 15 , 35 , 39 , 44 ], aseptic loosening [ 15 , 31 ], stump complications [ 28 , 34 ], failed rehabilitation [ 43 ], and suboptimal implant positioning [ 47 , 48 ]. Amanatullah et al [ 15 ] reported a high overall percentage of complications (28.6%), with periprosthetic fracture (14.3%) and dislocation (8.6%) accounting for the majority.…”
Section: Resultsmentioning
confidence: 99%